Problem-Solving with Python: Modeling of Lanthanide-Shift Reagent Complexes - Zlatković, Dragan; Đorđević Zlatković, Miljana; Radulović, Niko (Journal of chemical education, 2023)
Herein, we present a program implemented in Python that utilizes a simple complete-search algorithm to determine the geometry of a lanthanide–substrate (LS) complex. The program serves as a practical project in a programming course for chemistry students, specifically aimed at illustrating fundamental concepts such as decision-making, repetition, functions, lists, and file reading. The project challenges students to determine the position of a lanthanide ion in an LS complex by utilizing NMR titration experimental data obtained from the interaction between menthol and Eu(fod)3. Through the development of an algorithm and the creation of a Python program, students are tasked with calculating the optimal Eu position that correlates best with the experimental data. The primary objective of this project is to enhance students’ understanding of Python’s basic concepts, syntax, and problem-solving skills, fostering their growth in the field of chemistry programming.